Tracing the absence of a feminist agenda in gendered spiritual ecology: ethnographies in French-speaking Switzerland - Irene Becci; Alexandre Grandjean (Antropologia)
On the basis of ethnographic conversations and observations made among ecospiritual activists in French-speaking Switzerland, this text aims to locate the discourses and practices regarding gender references, following Linda Woodhead’s framing (2013). The observed gendered spiritual ecology fosters essentialized gender roles and values over the Feminine and the Masculine. The case description, one gendering a representation of nature and the other attaching gendered values to human attitudes in order to explain social and environmental disorders, is followed by a discussion of the assumption that essentialization could be a performative strategy for claims over new gender roles, thus depending on the social location of these religious actors. In conclusion, a larger theoretical perspective is offered referring to queer ecology and it’s attempt to overcome the nature/culture divide. The authors consider performance and materiality as two key-concepts to better understand the gender roles being promoted in ecospirituality and ecofeminist movements.